2016
DOI: 10.18632/oncotarget.9743
|View full text |Cite
|
Sign up to set email alerts
|

Virus-stimulated neutrophils in the tumor microenvironment enhance T cell-mediated anti-tumor immunity

Abstract: The tumor microenvironment (TME) fosters tumors by attenuating anti-tumor immunity, reinforcing tumor cell survival and increasing angiogenesis. Among the constituents of the TME, here, we focused on tumor-associated neutrophils (TANs). First, we found that the combination of poly I:C and inactivated Sendai virus particles (hemagglutinating virus of Japan envelope; HVJ-E) synergistically suppressed tumor growth in the B16-F10 melanoma mouse model. In this model, poly I:C contributed to the recruitment of CD11b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
(63 reference statements)
1
28
0
Order By: Relevance
“… 42 , 43 The anti-tumorigenic influence of virus-stimulated neutrophils is also reported in the B16F10 syngeneic tumor model. 44 …”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 The anti-tumorigenic influence of virus-stimulated neutrophils is also reported in the B16F10 syngeneic tumor model. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased TANs in mesenchymal tumors might contribute to the extreme immunosuppressive environment and plausibly mediate immunotherapy resistance. In contrast, Chang et al reported that virus-stimulated neutrophils in the tumor microenvironment increase T cell-mediated antitumor immunity in a mouse model of melanoma [78]. Although TANs are associated with an immunosuppressive environment within the tumor, clear experimental and clinical evidence is lacking to establish the involvement of TANs in immunotherapy outcomes, which is likely context dependent.…”
Section: Immunotherapy Resistancementioning
confidence: 98%
“…This virus, also known as hemagglutinating virus of Japan, is a restricted pathogen in rodents, producing transmissible respiratory tract infections. SV was evaluated in vitro and in vivo as an oncolytic for human cancers, mainly in colon carcinoma, melanoma, and glioblastoma [ 76 , 77 , 78 ]. In one study, SV was evaluated in vivo in six dogs as therapy for mastocytoma.…”
Section: Oncolytic Viruses For Canine Cancer Treatmentmentioning
confidence: 99%